Peningkatan Kesehatan Gigi dan Mulut dengan Budaya 4 Tepat 5 Sempurna di Jorong Gurun Aur - Muhammad Faisal; Eka Sukanti; Dewi Susanti; Dewi Rosmalia (CV. CENDIKIA JENIUS INDONESIA, 2024)
This community service program aimed to improve oral and dental health among the residents of Jorong Gurun Aur, Kenagarian Kubang Putih, Kecamatan Banuhampu, Kabupaten Agam. The main issue addressed was the lack of knowledge regarding proper toothbrushing techniques, which contributed to high cases of dental caries and other oral health problems. The program involved 13 elderly participants, 12 mothers with toddlers, and 52 TPA students. Activities included health education, demonstrations of toothbrushing techniques using the